Gender Differentials in Intimate Partner Abuse and Therapeutic Effectiveness of Self-Talk Therapy in reducing Anxiety Induced Among Undergraduates of Obafemi Awolowo University, Ile-Ife, Nigeria. - Obisakin, Emmanuel Makanjuola; Ojo, Olubukola Olakunbi (Advances in Social Sciences Research Journal, 2020)
ABSTRACT This study investigated the prevalence and determined forms of intimate partner abuse (IPA) common to undergraduates of Obafemi Awolowo University (OAU), Ile-Ife, Nigeria. It also investigated the gender differentials (Gender Symmetry and Asymmetry) in the perpetration of IPA among undergraduates and assessed the therapeutic effectiveness of self-talk therapy in reducing anxiety associated with IPA. The study adopted a mixed-method research design incorporating both descriptive survey and pretest-posttest control group experimental research designs. The sample for the descriptive survey was 1,448 undergraduates using the Sample Determination Table (Bartlett, II, Kotrlik & Haggins, 2001), which represents 6.5% of the total of undergraduates in OAU. The sample for the experimental stage of the study consisted of 32 undergraduates victims of IPA induced anxiety. Questionnaire on Prevalence and Types of Intimate Partner Abuse (QPTIPA) was used to collect data for the first stage of the study while the Beck Anxiety Inventory (BAI) was used to determine the levels of anxiety experienced by undergraduate victims of intimate partner abuse. Self-talk therapy was administered on the victims of IPA induced anxiety. The results showed that more females experienced intimate partner abuse of 74.76%, than male victims at 25.24%. The results also showed that “Stalking”, “Exploring partner's vulnerability/disability/status”, “Presenting false information with intent to exploit partner” were the first three in rank of the forms of IPA common among the undergraduates with RSI scores of 0.547, 0.529, and 0.527 respectively. The three least common forms were “beating”, “physically restraining Partner’s movement” and “forcing partner to have sex with someone else” with RSI scores of 0.475, 0.465, and 0.406 respectively. The study further revealed that Self-talk therapy has a significant effect (F (1, 64) = 63.360, p < 0.05) in reducing anxiety induced by IPA.Dr